Theoretical Aspects of the Formation of Intercultural Competence of Students Based on Blended Learning Technology - qizi, Nurmetova Mohimjon Ortiq (Research Parks Publishers, 2023)
The article describes issues based on the development of intercultural competence based on blended learning technology, describes the history of the development of intercultural communication, intercultural competence and blended learning, the relationship between communication and culture, including values. The technology of blended learning is being developed in the process of forming the intercultural competence of foreign students, using the Internet in synchronous and asynchronous modes; the forms and the definition of blended learning technology are characterized.